Board of Directors Size, Audit Committee Activities, and Audit Committee Size toward Earnings Management: Ukuran Dewan Direksi, Aktivitas Komite Audit, dan Ukuran Komite Audit terhadap Manajemen Laba - Mei Rinta (Journal of Accounting Science, 2021)
In accordance with the agency theory that management is responsible to the owner, so he will try to keep the performance of financial statements is always good and will act opportunistically to manage earnings if the performance of financial statements shows a decline. Therefore, the role of the board of director and audit committee is needed to protect the interests of the owner and manager. This study aims to investigate the effect of board of directors size, audit committee activities and the size of the audit committee on earnings management. This study uses a quantitative approach using secondary data from 322 samples of companies in the manufacturing sector during the period 2015-2017. The data collected was tested using multiple linear regression analysis techniques. This study produces findings that the size of the board directors have an insignificant negative effect on earnings management, the activities of the audit committee have a significant negative effect on earnings management and the size of the audit committee have an insignificant positive effect on earnings management. Keywords: Board Directors Size, Audit Committee Activities, Audit Committee Size, Earnings Management.